2003
DOI: 10.1021/la034219d
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Poly(n-butyl acrylate) from a Functionalized Carbon Black Surface by Atom Transfer Radical Polymerization

Abstract: The functionalization of a carbon black surface with atom transfer radical polymerization (ATRP) initiating sites and subsequent ATRP of n-butyl acrylate (n-BA) from the surface of carbon black is reported. The polymerizations were carried out using CuBr/N,N,N′,N′,N′′-pentamethyldiethylenetriamine and CuBr2/ 4,4′-di(5-nonyl)-2,2′-bipyridine as the catalytic system at 70 °C. A significant amount of polymers was attached to the carbon black as determined by thermogravimetric analysis and light scattering experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 41 publications
1
71
0
2
Order By: Relevance
“…[33,122,123] The synthesis of carbon black grafted with pBA chains was conducted by surface-initiated ATRP from functional carbon black surfaces. [124] Analysis of pBA chains cleaved from the cores indicated that polymers with tunable molar mass and low polydispersity (M n ¼ 48 450; M w =M n ¼ 1.33) were obtained. AFM of pBA-coated carbon black particles cast onto mica (Figure 9) confirmed the efficient grafting of pBA onto the central core, with morphologies consistent with those observed for other pBA spherical brushes (see Figure 6).…”
Section: Modification Of Carbon Black Fillersmentioning
confidence: 99%
“…[33,122,123] The synthesis of carbon black grafted with pBA chains was conducted by surface-initiated ATRP from functional carbon black surfaces. [124] Analysis of pBA chains cleaved from the cores indicated that polymers with tunable molar mass and low polydispersity (M n ¼ 48 450; M w =M n ¼ 1.33) were obtained. AFM of pBA-coated carbon black particles cast onto mica (Figure 9) confirmed the efficient grafting of pBA onto the central core, with morphologies consistent with those observed for other pBA spherical brushes (see Figure 6).…”
Section: Modification Of Carbon Black Fillersmentioning
confidence: 99%
“…Surface-initiated polymerizations are the most frequently used methods to covalently connect polymer chains to the surface of a material, which are based on the so-called "grafting from" technique [9,10]. Significant advances in this area have been achieved by the development of living radical polymerization techniques, especially as nitroxide-mediated polymerization (NMP) [11,12], reversible addition-fragmentation chain transfer polymerization (RAFT) [13], and atom transfer radical polymerization (ATRP) [14].…”
Section: Introductionmentioning
confidence: 99%
“…This linear relation between the PG and reaction time indicated that this polymerization had a good characteristic of controlled/living radical polymerization. 33 Therefore, the length of chains of the grafted polymers could be adjusted by controlling the polymerization time. Thus, the proposed method on the basis of the continuous flow-through technique could be proved to be successful in the application of surface-initiated AGET ATRP.…”
Section: In Situ Grafting Copolymerization Of Nipaam By Aget Atrpmentioning
confidence: 99%